The Characteristics Probabilities and Risks Prediction of Containers as Potential Breeding Sites for Aedes Aegypti Mosquitoes - Ahmad Rasyid Ridha Ramadhan; Nurul Hidayah; Muhammad Husni (Lambung Mangkurat, 2022)
Characterization of the Aedes aegypti larval container is an important factor influencing mosquito reproduction patterns and is an important aspect of integrated vector control. The study purpose to identify the characteristics and predict the risk of water reservoirs that have the potential as a breeding place for the Aedes aegypti mosquito. The study was using descriptive with a quantitative approach. It was conducted in the West Banjarmasin District which consisted of 9 villages (Kuin Selatan, Kuin Cerucuk, Belitung Selatan, Pelambuan, Belitung Utara, Telaga Biru, Telawang, Teluk Tiram, and Basirih). The population was all households in West Banjarmasin District with a total of 10.003 houses. A sample of 100 houses was taken using proportional random sampling. The results showed that 77.8% of households use tap water sources and there are 44,4% use dark colored containers. Most of the households have a water reservoir in the house (88.9%) and in Teluk Tiram Village about 66.70% of the households drain the water reservoir for more than 7 days. Concluded that the characteristics of most water reservoirs were tap water sources, dark in color, located inside the house, and cleaned more than 7 days with the highest risk value was 73.13%.